Decoding Islamic Marriage Terms Through Quranic Text by Nvivo 12 Pro - Abdullah, Muhammad Yahya; Insan Kamil (Jurnal test, 2024)
This research is motivated by the recognition of two word roots that can refer to the concept of marriage in fiqh literature, namely the roots of the words “zawaja” and “nakaha”. The aim of this research is to examine and map every term and meaning contained in every verse of the Koran which contains these two word roots to find the meaning of the term marriage in an Islamic perspective through the text of the Koran. The research method used is qualitative design with the aid of Nvivo 12 Pro as a supporting application for analyzing and categorizing these verses. The results of this research reveal that there are eight terms found through tracing all the verses containing these two word roots in the Koran, four terms constructed to the concept of marriage, namely the term prohibition in marriage, the term ethics in divorce, the term marriage regulations and the term of marriage’s lessons. Apart from that, there are also four other terms which are not correlate to the concept of marriage, namely the term signs of God's power, the term stories of wisdom, the term various rewards and other laws.